Bipolar disorder in the postpartum period: management strategies and future directions. (July 2014) - Pope, Carley J; Sharma, Verinder; Mazmanian, Dwight
Bipolar I and II disorder are chronic and severe psychiatric illnesses that affect many women. Furthermore, women are at increased risk for mood episodes during the postpartum period compared with non-postpartum periods. Unfortunately, identification of clinically significant depressive or (hypo)manic episodes can be challenging. Delays in detection, as well as misdiagnosis, put women at risk of many negative consequences, such as symptom exacerbation and treatment refractoriness. Early and accurate detection of bipolar I or II disorder in the postpartum period is critical to improve prognosis. At this time, limited recommendations can be made due to a paucity of research. Further research on postpartum bipolar I or II disorder focusing on its identification, consequences and treatment is urgently needed to allow for empirically informed clinical decision-making.